Nanodrugs Detonate Lysosome Bombs - Xiang, Yuting; Li, Niansheng; Liu, Min; Chen, Qiaohui; Long, Xingyu; Yang, Yuqi; Xiao, Zuoxiu; Huang, Jia; Wang, Xiaoyuan; Yang, Yunrong; Zhang, Jinping; Liu, Chong; et al. (Frontiers in Pharmacology, 2022)
Cancer cell lysosomes contain various hydrolases and non-degraded substrates that are corrosive enough to destroy cancer cells. However, many traditional small molecule drugs targeting lysosomes have strong side effects because they cannot effectively differentiate between normal and cancer cells. Most lysosome-based research has focused on inducing mild lysosomal membrane permeabilization (LMP) to release anticancer drugs from lysosomal traps into the cancer cell cytoplasm. In fact, lysosomes are particularly powerful “bombs”. Achieving cancer cell-selective LMP induction may yield high-efficiency anticancer effects and extremely low side effects. Nanodrugs have diverse and combinable properties and can be specifically designed to selectively induce LMP in cancer cells by taking advantage of the differences between cancer cells and normal cells. Although nanodrugs-induced LMP has made great progress recently, related reviews remain rare. Herein, we first comprehensively summarize the advances in nanodrugs-induced LMP. Next, we describe the different nanodrugs-induced LMP strategies, namely nanoparticles aggregation-induced LMP, chemodynamic therapy (CDT)-induced LMP, and magnetic field-induced LMP. Finally, we analyze the prospect of nanodrugs-induced LMP and the challenges to overcome. We believe this review provides a unique perspective and inspiration for designing lysosome-targeting drugs.